2020
DOI: 10.1002/fsn3.1598
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Konjac glucomannan on the functional and structural properties of wheat starch

Abstract: The aim of this study was to characterize the influence of Konjac glucomannan (KGM) on the functional and structural properties of wheat starch. Results showed that KGM significantly decreased the starch hydrolysis rate, with a lower level of rapidly digestible starch (RDS), and a higher content of slowly digestible starch (SDS). Besides, KGM decreased the content of leached amylose, while enhanced the swelling power, water‐holding capacity, freeze‐thaw stability, and paste clarity of wheat starch, which indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Following the addition of DFP (250 mg), the characteristic peaks in all flours were shifted to lower wavenumbers, indicating the interaction between starch and DFP. These interactions were also observed when mixing phenolic compounds, proanthocyanidins, and soluble dietary fiber with flour, causing a reduction in starch digestibility [ 21 , 37 ]. In general, the ratio of the bands at 1047, 1022, and 1000 cm −1 represents crystalline and amorphous structures in starch, which refer to amylose and amylopectin content and affect the starch digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…Following the addition of DFP (250 mg), the characteristic peaks in all flours were shifted to lower wavenumbers, indicating the interaction between starch and DFP. These interactions were also observed when mixing phenolic compounds, proanthocyanidins, and soluble dietary fiber with flour, causing a reduction in starch digestibility [ 21 , 37 ]. In general, the ratio of the bands at 1047, 1022, and 1000 cm −1 represents crystalline and amorphous structures in starch, which refer to amylose and amylopectin content and affect the starch digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, the swelling of the starch granules was restricted in the presence of KGM [ 39 ]. On the one hand, KGM competed with starch for water molecules and reduced the growth of the starch granules [ 40 ]. On the other hand, the acetyl groups were removed from KGM in a heated alkaline environment [ 21 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that tannic acid reacted with starch granules and altered their physicochemical properties (e.g., gelatinization and retrogradation) and the microstructure properties, and demonstrated tannic acid reduced the starch digestion by enzyme inhibition and the changed structures (Zeng et al., 2020 ). Konjac glucomannan also played an important role in the microstructure of wheat starch and its digestibility, which acted by forming a barrier around the granules (Zhang et al., 2020 ). Similar result was also found by κ‐carrageenan in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental groups, the addition ratio of konjac glucomannan (KGM) and κ‐carrageenan (KC) was 3%, and the addition ratio of tannic acid (TA) was 0.2%. The concentrations of KGM, KC, and TA were chosen according to the preliminary experiments and the reference (Zeng et al., 2020 ; Zhang et al., 2020 ). The mixing percentages of added substances were based on the mass ratio of wheat starch ( w/w ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation